Using a String Scar Marker with Iodine for CT Simulator in Breast Cancer Cases: Penggunaan String Scar Marker dengan Yodium untuk CT Simulator Kasus Kanker Payudara - Veasna, Bun; Nurbaiti, Nurbaiti; Heru Apriantoro, Nursama (JURNAL ILMU DAN TEKNOLOGI KESEHATAN TERPADU, 2024)
Breast radiotherapy in breast cancer patients often uses CT landmark wires to pinpoint the area of ​​breast scars for appropriate treatment. Most commercial CT marker wires are expensive and made of high-Z materials that cause scratch artifacts. In hospitals, scar markers are made from nylon string with an iohexol contrast medium. This research aims to analyze a simulation of a CT examination in breast cancer cases using a string scar marker with iodine and analyze its characteristics. For this reason, the authors created a new breast CT scar marking wire using nylon rope combined with iodine contrast media in CT simulations of breast cancer cases for treatment planning. Three patients were scanned using a string scar marker developed with iodine for breast cancer in the hospital's CT simulator facility. As a result, using a computer console, the CT number showed this string scar marker had clear visibility and did not produce artifacts. In conclusion, this new string breast scar marker is fast, flexible, and inexpensive. This is beneficial for the treatment of breast cancer patients.